"I Thought I Did Much Better"—Overconfidence in University Exams. (15th October 2018) - Wüst, Kirsten; Beck, Hanno
ABSTRACT: Students tend to be overconfident about their future performance in university exams, which can lead to demotivation when faced with unexpectedly bad results. We hypothesized that overconfidence is partly a personality trait but also partly results from students' insufficient knowledge of what is expected of them in university exams. It follows that this should decrease as the students learn what is really required. In a longitudinal study with 441 students from a southern German university, we asked students to solve intelligence test questions and to make estimates of their own performances. Additionally, students estimated their performance in a forthcoming maths and/or a descriptive statistics exam. Then shortly after the exam was taken they indicated their planned and effective hours of study. As expected, students did not, in the mean, overestimate their performance on intelligence test questions. Women were more likely than men to underestimate their performance. Over‐ or underestimation in intelligence test questions did, however, predict misestimation in the mathematics and the statistics exams. Also, further correlations of misestimation between the statistics and a financial mathematics exam could be found—as such misestimation can be interpreted to be a stable trait. Students with an "Abitur" qualification were more likely to underestimate their performance, while students with other preuniversity qualifications tended to overestimate their performance. No effect of personality factors was found. Against our expectations, students who had overestimated themselves later indicated a higher number of hours studied than other students. We suggest different strategies by which students and universities can actively counter overestimation.